The importance of using geophysical methods in shallow investigations for natural or artificial structures - ΠΑΠΑΔΟΠΟΥΛΟΣ, ΤΑΞΙΑΡΧΗΣ (Bulletin of the Geological Society of Greece, 2002)
In this review paper it is presented the usefulness and importance of using geophysical methods in shallow subsurface investigations. It is given emphasis on problems that can be handled by the engineering and environmental geophysics which are branches of applied geophysics. First, the geophysical methods that are mainly used are referred, their efficiency, as well as the potentialities and restrictions that they present. Next, some basic topics are defined that the geophysicist has to take into account in order to end up with positive results. Finally, the advantages and disadvantages of the most used geophysical methods are referred and some examples are given from the experience obtained by carrying out geophysical investigations in Greece